EFFECT OF Rosemarinus officinalis PLANT AND H2O2 1% ON SOME PHYSIOLOGICAL , HISTOLOGICAL AND BIOCHEMICAL PARAMETERS IN MALE Mus musculus - RAJA MUSTAFA AL-ANNAZ (Mesopotamia Journal of Agriculture)
This study was conducted to investigate the effect of Rosemarinus officinalis powder 10g/kg food against the oxidative stress induced by 1% H2O2 in drinking water in mature male mouse two month aged (25-30 ) gm in weight . The oxidative stress was determined by measuring the level of glutathione ( GSH ) and the level of malondialdehyde (MDA) in liver tissue , The study also evaluate the effects of 1% H2O2 on biochemical and hematological parameters . The mousse are divided into four groups, 6 mouse / gp and treated for two months , the first group is the control while the second is treated with Rosemary alone and the third treated by 1% H2O2 with drinking water and standard food and the last group is treated with Rosemary 10 g/kg with 1% H2O2 in drinking water. The result revealed that the powdered Rosemary have an antioxidant activity which cause refreshing in hematology parameters ( R.BC , W.B.C ,Hb, P.C.V.) . as compared with control and increase the level of ( GSH ) and a significant decrease in level of ( MDA (. Results of this study remarked the scientific phenomenon that the uses of plants that have antioxidant activities such as Rosemary dealing a good protection from the oxidative stress .